Síntese e funcionalização de compostos heterocíclicos visando a descoberta de fármacos antivirais - Santos, Jhonathan Renner Nunes dos (Universidade Federal de São Carlos, 2025)
The humanity has faced numerous viral epidemics, significantly impacting daily life. Notable examples include infections caused by dengue and Zika virus, as well as the COVID-19 pandemic caused by the SARS-CoV-2. In this respect, the scientific community mobilized a task force to develop vaccines and new therapies. Drug repurposing also played a crucial role during this period, as seen with remdesivir, a C-glycoside originally developed to combat the Ebola virus, that became one of the first drugs approved for emergency use against SARS-CoV-2. Despite having a well-established synthetic route, remdesivir production still posed challenges, prompting various research groups to optimize steps with low yields or harsh reaction conditions. In this context, the objective of this thesis was to synthesize C-glycoside analogs using more sustainable methods, such as C-H functionalization of N-heterocycles via photochemical processes and multicomponent reactions. Once these compounds were synthesized, their biological activity was evaluated against the proteases Mpro and PLpro of SARS-CoV-2 and NS2B-NS3Pro of the Zika virus. Concerning the C-H functionalization of N-heterocycles, 14 compounds were synthesized, with yields ranging from 10% to 81%. The developed protocol demonstrated to be regioselective, enabling the formation of a C-C bond at the C-7 position of pyrrolo[2,1-f][1,2,4]triazine. Then, 38 compounds were obtained, including derivatives of dihydropyrimidine-2(1H)-ones/thiones (DHPMs), coumarins, DHPM-coumarin hybrids, and coumarin dimers. These compounds have demonstrated potential in inhibiting the viral activity of SARS-CoV-2 and the Zika virus. For SARS-CoV-2, seven compounds showed promising activity against the Mpro enzyme, with IC50 values ranging from 4.8 to 87 µM. Six compounds exhibited effectiveness against PLpro, with IC50 values between 21 and 81 µM. Regarding the Zika virus NS2B-NS3Pro, seven compounds displayed activity, with IC50 values ranging from 0.4 to 7.1 µM. In summary, this study successfully identified potential enzymatic inhibitors for SARS-CoV-2 and Zika virus proteases using more sustainable approaches, including photochemistry and multicomponent reactions. Further studies may be conducted to enhance the efficacy of these compounds.
Synthesis and functionalization of heterocyclic compounds aiming at the discovery of antiviral drugs
Keywords: Inibidores enzimáticos; RMCs; SARS-CoV-2; ZIKV; Fotoquímica; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA